PTH-146 Impact of haemoglobin on survival in oesophagogastric cancer: haemoglobin at diagnosis and prior to surgery predicts survival. (22nd June 2015) - Ng, O; Oakley, B; Holmes, S; Parsons, S; Catton, J; Madhusudan, S; James, E; Brookes, M; Acheson, A
Abstract : Introduction: Anaemia is common in oesophagogastric cancer. Major operations performed for these cancers are associated with significant blood loss and need for transfusions. Concerns exist about the side effects of blood transfusion, cost and availability of donated blood. Our study aims to identify incidence of anaemia, change in haemoglobin, rates of blood transfusion and mortality associated with the diagnosis and treatment of oesophagogastric cancer. Method: We conducted a retrospective analysis of all patients diagnosed with oesophagogastric cancer in 2012–2013 at a single high-volume referral centre. Data was collected on site, histology, staging, haemoglobin, blood transfusions, survival and treatment. WHO definitions were used to define anaemia. Results: 550 patients were included in the study. Median haemoglobin at time of diagnosis was 127 g/L (37–188 g/L). 227 patients (45%) were anaemic at diagnosis. Higher haemoglobin at diagnosis improved survival (irrespective of a diagnosis of anaemia) with high normal haemoglobin (>150 g/L) showing significantly better survival than low normal haemoglobin (130–150 g/L), p < 0.001. Mild anaemia (110–130 g/L) had significantly poorer survival again but superior to moderate and severe anaemia (p < 0.05 Breslow-Wilcoxon). Anaemia prior to surgery was also associated with poorer survival (p < 0.05). In the 233 patients treated with surgery, 86 (38.9%) were anaemic at diagnosis. However, this increases to 144 patients (66.9%) prior to surgery and 203 (93.9%) post-operatively. If anaemic prior to curative surgery patients were 29.5% more likely to receive a blood transfusions. Logistic regression analysis revealed male sex, anaemia at diagnosis and neoadjuvant chemotherapy correlated with pre-operative anaemia (p < 0.05). Staging was not a predictor of anaemia. Neo-adjuvant chemotherapy increased the number of patients who were anaemic prior to surgery by 26.5% and the average drop in haemoglobin to 15 g/L compared to 5 g/L for those who went straight to surgery. Conclusion: Anaemia is common in oesophagogastric cancer and becomes worse during treatment. Neoadjuvant treatment increases the rates and severity of anaemia. Lower haemoglobin at diagnosis and anaemia prior to surgery are both associated with poorer survival and more blood transfusions. A more proactive strategy to the management of anaemia is required if we are to attempt to avoid the excess mortality and blood transfusions seen here in oesophagogastric cancer. Disclosure of interest: None Declared.